Anti-candida activity of methanolic oroxylum indicum leaves extract against candida species - Rahman, Amalina Ab (Universiti Sains Malaysia, 2024)
Oroxylum indicum has been used traditionally to treat common ailments and its leave extract has been reported to possess antimicrobial properties. The aim of this study was to evaluate the in-vitro anti-Candida activity of Oroxylum indicum leaves extract against selected Candida species. Methanolic leaves extract of Oroxylum indicum was tested for anti-Candida activity against C. albicans, C. tropicalis, C. parapsilopsis, C. krusei, and C. glabrata. Anti-Candida activities were evaluated by well-diffusion method and the minimum inhibitory concentrations (MIC) were determined using the two-fold serial broth microdilution technique of concentration ranging from 500.0 mg/mL to 3.9 mg/mL. After 24 hours of incubation, the minimum fungicidal concentration (MFC) was determined by sub-culturing the wells which showed no turbidity onto Sabouraud dextrose agar (SDA). The presence of potential phytochemicals group in the crude extract was screened by phytochemical qualitative tests. The methanolic extract showed moderate (50% of inhibition zone) anti-Candida activity against C. albicans and C. krusei. C. albicans was the most susceptible among the tested Candida species and showed a low MIC value (78 mg/mL). The extract was also fungicidal to C. albicans (MFC/MIC ratio of 4.0). Flavonoid, tannin, triterpenoid and steroid were the major phytochemicals of the crude extract. This study suggested that methanolic Oroxylum indicum leaves extract has weak anti-Candida activity.